Risk Management in a Practical Philosophical Perspective: Implications for Organizational Leadership - Hamzah, Amir; Dini, Maya; Muhardi, Muhardi (Journal of Social Science and Business Studies, 2026)
This study aims to develop a philosophical reinterpretation of risk management and to examine its implications for organizational leadership. Using a conceptual and philosophical research design, the study is based on a systematic review and integrative synthesis of literature on risk management, leadership, and practical philosophy, particularly Aristotelian ethics and the concept of phronesis. The analysis indicates that dominant risk management models are largely grounded in instrumental rationality and are limited in addressing ethical ambiguity, contextual judgment, and moral responsibility in decision-making under uncertainty. As a result, this study develops a conceptual framework that emphasizes practical wisdom, ethical reasoning, and leadership sensemaking as core elements of effective risk governance. The study concludes that risk management is fundamentally a moral and interpretive activity embedded in leadership practice, and that integrating practical philosophy into risk management complements existing technical models while strengthening ethical accountability, strategic decision-making, and organizational resilience.